1994
DOI: 10.1002/ar.1092400114
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of glutamate immunoreactivity in lemniscal terminals in the ventropostero lateral thalamic nucleus of the rat: An immunogold and WGA‐HRP study

Abstract: These findings are in agreement with several lines of evidence, obtained with different experimental approaches, supporting the hypothesis that Glu plays a major role in conveying sensory stimuli to the thalamus from second order neurons in the dorsal column nuclei.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…In particular, in neonatal VB the ascending terminals were not distinguishable from terminals of other sources as they are in adults De Biasi et al 1988, 1994a. Previous light microscopic tracing studies reported that, by the day of 351 birth, ascending fibers have already reached their thalamic target, where they ramify extensively (Belford and Killakey 1982;Asanuma et al 1988).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, in neonatal VB the ascending terminals were not distinguishable from terminals of other sources as they are in adults De Biasi et al 1988, 1994a. Previous light microscopic tracing studies reported that, by the day of 351 birth, ascending fibers have already reached their thalamic target, where they ramify extensively (Belford and Killakey 1982;Asanuma et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The centers related to the visual pathways are among the areas that have been more extensively investigated (Wienfield and Powell 1980;Mason 1982;Campbell et al 1984;Holstein et al 1985;Weber and Kalil 1987;Campbell and Shatz 1992;Khan et al 1994), whereas relatively little information is available on the postnatal development and differentiation of two of the thalamic nuclei involved in the processing of somatosensory inputs, i.e., the VB and Rt nuclei. These nuclei represent a convenient model system because their synaptic circuitry and neurochemical content have been extensively investigated in the adult and in rats it has been shown that they have a much simpler organization than in other mammals (McAllister and Wells 1981;Lieberman 1981, 1985;De Biasi et al 1986, 1994aMa et al 1987;Rustioni et al 1988;Rustioni and Weinberg 1989;De Biasi and Rustioni 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous early studies demonstrated that glutamate is the neurotransmitter of all these excitatory thalamic inputs (Haldeman and McLennan, 1972;de Biasi et al, 1994; reviewed by Salt and Eaton, 1996). Recent neuropharmacological findings have shown that the ascending excitatory afferents to both the ventral posterior and lateral geniculate nuclei (LGN) elicit responses in relay neurons that are sensitive to both non-N-methyl-D-aspartate (NMDA) and NMDA receptor antagonists.…”
mentioning
confidence: 99%
“…The specificity of the antisera against PV and GABA has been previously characterized (Celio, 1990;De Biasi et al, 1994). Method specificity both for PV and GABA immunolabelling was controlled by the application of rabbit nonimmune serum as well as by the processing of a series of sections omitting various stages from the regular staining sequence.…”
Section: Immunocytochemical Controlsmentioning
confidence: 99%